2014
DOI: 10.1007/s40477-014-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic findings in Crohn’s disease

Abstract: In recent years transabdominal bowel sonography has become a first-line modality both in the diagnosis and in the follow-up of inflammatory bowel diseases, especially Crohn's disease, reaching values of sensitivity ranging from 84 to 93 %. In particular, its role is very useful in the early diagnosis of complications such as stenosis, phlegmons, abscesses and fistulae. According to the available literature the ability of US to provide information about disease activity is still under debate and further studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previous NIRS measuring devices were used to evaluate adults’ cerebral blood flow to a depth of 1–3 cm [ 9 , 24 , 25 ], but these devices are unsuitable for assessing intestinal tissue. The thickness of the small intestinal wall is less than 3 or 4 mm, therefore the depth of measurement with previous NIRS devices was considered to be too deep [ 26 , 27 ]. Recently, the cerebral blood flow of infants or the placental oxygen saturation of fetuses were analyzed using advanced technology of NIRS [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous NIRS measuring devices were used to evaluate adults’ cerebral blood flow to a depth of 1–3 cm [ 9 , 24 , 25 ], but these devices are unsuitable for assessing intestinal tissue. The thickness of the small intestinal wall is less than 3 or 4 mm, therefore the depth of measurement with previous NIRS devices was considered to be too deep [ 26 , 27 ]. Recently, the cerebral blood flow of infants or the placental oxygen saturation of fetuses were analyzed using advanced technology of NIRS [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…He also reported that significant increase in the mean sum of thickness of the submucosa, muscularis, muscularis and serosa was noted and in humans with Crohn's Disease has similar findings. In accordance with Maffe et al (2015) bowel is considered to be thickened when the measurement of the wall is more than 3mm and opined that ultrasonography helps in identification of extra intestinal features associated with active Crohn's Diseases, such as mesenteric fat hypertrophy, enlarged regional lymph nodes and free fluid accumulation in intraperitoneal free fluid. He also suggested that stenoic intestine has a thickened wall, narrow lumen along with reduced or on peristalsis and associated with pre-stenoic dilatation greater than 25 mm in diameter with liquid and air in Lumen.…”
Section: Ultrasonographic Evaluation Of Gastro-intestinal Dysfunction...mentioning
confidence: 99%
“…(5) Presence of fistula signs (Figure 5). Fistula signs were defined as a hypoechoic, duct-like, peri-intestinal lesion with a diameter smaller than 2 cm, sometimes with internal echoic spots related to the presence of air, debris, or intestinal material [20].…”
Section: Baseline Data Processing and Ultrasonic Feature Extractionmentioning
confidence: 99%